ANALISIS KEMAMPUAN SISWA KELAS V SD GUGUS I KECAMATAN SUKAJADI KOTA PEKANBARU DALAM MENGANALISIS UNSUR INTRINSIK CERPEN - Liya Liya; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is motivated by the problem of the student in analyzing elements. Many of students have problems in analyzing because of lack of understanding about intrinsic elements, where the students just read without understanding the content of the reading text. Besides the lack of the students understanding, the researcher also found information that lack of exercises in analyzing intrinsic elements, so that it is difficul for the students to analyzing intrinsic elements of short story. The objective of the research is to describe the fifth grade student’s ability at SD Gugus I Sukajadi subdistrict Pekanbaru analyzing intrinsic elemets of short story. This research is descriptive quantitative research. The method of the reaserch is survey method by collecting the data using test in the from of essay as much 6 questions that have been validated use judgment validation expert. The population of the reaserch are 242 students. The sample of the research was taken 5% so the sample of the reaserch are 142 students. Based on the result of the reaserch, it can be concluded that the fifth garde struden’s ability at SD Gugus I Sukajadi subdistrict Pekanbaru in analyzing intrinsict elements of short story by 142 students as a sample in this reaserch who could reach an axcellent level are 31 students, good level are 102 student, average level are 8 students and the student who get poor level is 1 student with an average rating score is 76,6 by the following indicators as follows: 1) on the theme indicator whit everage level is 61,25. 2) on the fugure indicator whit exellent level is 97,75. 3) on the setting indicator whit good level is 84,5. 4) on the caracter indicator whit everage level is 64,75. 5) on the plot indicator whit excellent level is 90,25. 6) on the message indcatore whit average level is 62,25. Overall, the student’s ability get an everage score 76,6 with good level. It is shows that the fifth grade student’s ability SD Gugus I Sukajadi subdisrtict Pekanbaru in analizyng intrinsict elements of short story are in good level.Keywords: ability in analyzing short story intrinsisc elements.